The Local Exploration of Magnetic Field Effects in Semiconductors - Thien Thanh Dang; Juliana Schell; Reinhard Beck; Cornelia Noll; Doru C. Lupascu (Crystals, 2022)
This study reports on the local exploration of magnetic field effects in semiconductors, including silicon (Si), germanium (Ge), gallium arsenide (GaAs), and indium phosphide (InP) using the time differential perturbed angular correlation (TDPAC) technique. TDPAC measurements were carried out under external magnetic fields with strengths of 0.48 T and 2.1 T at room temperature, and 77 K following the implantation of 111In (111Cd) probes. Defects caused by ion implantation could be easily removed by thermal annealing at an appropriate temperature. The agreement between the measured Larmor frequencies and the theoretical values confirms that almost no intrinsic point defects are present in the semiconductors. At low temperatures, an electric interaction sets in. It stems from the electron capture after-effect. In the case of germanium and silicon, this effect is well visible. It is associated with a double charge state of the defect ion. No such effects arise in GaAs and InP where Cd contributes only a single electronic defect state. The Larmor frequencies correspond to the external magnetic field also at low temperatures.